Automatic face recognition in real-time - Lim, Chun Peng (2019)
With the rise of Internet of Things, the interest in face recognition increases as well. Real-time Automatic Face Recognition is a particularly attractive approach, as it focuses on the primary identifier that humans use to distinguish one person to the other. In this project, a small and compact system is implemented using the Nvidia Jetson TX2 developer module in conjunction with the You Only Look Once v3 algorithm. The report will go over specifications of the Nvidia Jetson TX2 and integration details with the YOLOv3 algorithm.